2012
DOI: 10.1002/etc.1777
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine disrupting, mutagenic, and teratogenic effects of upper Danube River sediments using effect‐directed analysis

Abstract: Effect-directed analysis (EDA) can be useful in identifying and evaluating potential toxic chemicals in matrixes. Previous investigations of extracts of sediments from the upper Danube River in Germany revealed acute nonspecific and mechanism-specific toxicity as determined by several bioassays. In the present study, EDA was used to further characterize these sediments and identify groups of potentially toxic chemicals. Four extracts of sediments were subjected to a novel fractionation scheme coupled with iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 39 publications
2
33
0
Order By: Relevance
“…For that, there was exposure of the zebrafish to compounds known to cause specific effects such as anti-convulsant activity [39], glucose uptake [45], pro-angiogenesis [36,37], antiangiogenesis [19,44], or estrogenic effects [52,56]. Regarding negative control conditions, most of the studies reported the testing of solvent controls in the same concentration as for the respective sample testing [19,32,34,35,[38][39][40]43,44,47,[49][50][51]53,55]. Some studies have additionally evaluated a medium only condition in addition to the solvent control [36,37,42,54,56,57].…”
Section: Positive/negative Controls and Biotesting Of Blanksmentioning
confidence: 99%
See 4 more Smart Citations
“…For that, there was exposure of the zebrafish to compounds known to cause specific effects such as anti-convulsant activity [39], glucose uptake [45], pro-angiogenesis [36,37], antiangiogenesis [19,44], or estrogenic effects [52,56]. Regarding negative control conditions, most of the studies reported the testing of solvent controls in the same concentration as for the respective sample testing [19,32,34,35,[38][39][40]43,44,47,[49][50][51]53,55]. Some studies have additionally evaluated a medium only condition in addition to the solvent control [36,37,42,54,56,57].…”
Section: Positive/negative Controls and Biotesting Of Blanksmentioning
confidence: 99%
“…When the application of multiple biossays aimed to evaluate distinct bioactivities, the tests were mostly performed in parallel. For instance, bioassay batteries evaluated the occurrence of different toxicity mechanisms [50,51] or effects on different trophic levels in the two TIE studies [32,33]. When instead the aim of multiple methods was to analyse different aspects of the same bioactivity or toxicity mechanism, there was the prevalence of tiered approach biotesting [19,39,45].…”
Section: Biotesting Strategymentioning
confidence: 99%
See 3 more Smart Citations